Long-Term Course of Polymorphic Light Eruption: A Registry Analysis - Gruber-Wackernagel, Alexandra; Schug, Tanja; Graier, Thomas; Legat, Franz J.; Rinner, Hanna; Hofer, Angelika; Quehenberger, Franz; Wolf, Peter (Frontiers in Medicine, 2021)
Background: Little is known about predictive factors for the long-term course of polymorphic light eruption (PLE). Objective: To predict disease course, a questionnaire was sent to patients whose PLE had been diagnosed between March 1990 and December 2018 and documented in the Austrian Cooperative Registry for Photodermatoses. Methods: In January 2019, 205 PLE patients were contacted by mail and asked to complete a questionnaire on their disease course, including whether the skin’s sun sensitivity had normalized (ie, PLE symptoms had disappeared), improved, stayed the same, or worsened over time. Patients who reported normalization of sun sensitivity were asked to report when it had occurred. Results: Ninety-seven patients (79 females, 18 males) returned a completed questionnaire. The mean (range) duration of follow-up from PLE onset was 29.6 (17-54) years for females and 29.4 (16-47) years for males. The disease disappeared in 32 (41%) females after 17.4 (2-41) years and in 4 (24%) males after 11.8 (5-26) years. Patients who reported having PLE lesions within 24 h after sun exposure under daily life conditions were less likely to report improvement or normalization of disease (odds ratio [OR], 0.12; 95% Cl, 0.01-0.72); patients whose skin lesions disappeared within 1 week were more likely to report improvement or normalization (OR, 3.20; Cl, 1.07-10.3). PLE onset, sex, skin phototype, and seasons with PLE manifestation had no statistically significant predictive value. Conclusions: This study identified predictive factors for the course of PLE. How those factors relate to the pathophysiology of the disease remains to be determined.